Control of surface forces through hydrated boundary layers. (December 2019) - Lin, Weifeng; Klein, Jacob
Abstract: Hydration layers surrounding charges or zwitterionic moieties have long been known to play important roles in areas including antifouling and colloidal stability, and particularly over the past 15 years or so, their role in boundary lubrication has been widely investigated. Hydration repulsion because of hydrated ions or polar groups present on surfaces may dominate their interactions at high electrolyte concentrations, so that Derjaguin–Landau–Verwey–Overbeek theory does not apply. Hydration shells, strongly held by the charges they surround, can sustain large pressures without being squeezed out, while by rapidly relaxing, and they behave like a fluid during shear; this may lead to their acting as lubrication vectors with outstanding friction–reduction properties. This review considers hydration layers around trapped ions, polymer brushes, and amphiphiles (surfactants and phosphatidylcholines), focusing on their lubrication properties. Finally, we suggest some prospects for further development of current hydrated vectors and designing new hydrated vectors for modifying surface interactions. Graphical abstract: Image 1